Flash Point Improvement of Mineral Oil Utilizing Nanoparticles to Reduce Fire Risk in Power Transformers: A Review - Khoirudin; Budi Kristiawan; Sukarman; Amri Abdulah; Budi Santoso; Agung Tri Wijayanta; Muhammad Aziz (Fire, 2024)
Transformers are crucial equipment in electrical distribution systems but have a significant potential for failure. Insulation materials, including transformer oil (TO), play a primary role in transformer failures. A fire involving the TO can lead to a large explosion, causing the main tank to rupture and resulting in extensive damage to the entire transformer and the surrounding area. Mineral oil (MO) is the most widely used type due to its availability and relatively low cost compared to other types of oil. However, MO has a critical disadvantage, which is its very low flash point. The low flash point makes MO highly flammable. When the oil fires in an enclosed space, such as a transformer tank, the pressure inside the tank increases, leading to a large explosion. Therefore, research on increasing the flash point of MO is highly necessary. The application of nanotechnology is a promising approach to increasing the flash point of base fluids. Research on the effect of nanoparticles (NPs) on flash points is very limited in the literature; thus, there is significant potential for further research in this field. The majority of studies indicate an increase in flash points with the addition of NPs to MO. There is only one study that shows a decrease in flash point, which is −1.33% compared to MO. From all the reviewed studies, it can be concluded that NPs are a potential solution to increase the flash point of MO. Despite their benefits, NPs require a thorough examination of health and environmental impacts, along with proper waste management, to ensure their advantages.